Reducing surgical site infections in low-income and middle-income countries (FALCON): a pragmatic, multicentre, stratified, randomised controlled trial. Issue 10312 (6th November 2021) - ,; Ademuyiwa, Adesoji O; Hardy, Pollyanna; Runigamugabo, Emmy; Sodonougbo, Pierre; Behanzin, Hulrich; Kangni, Sosthène; Agboton, Gérard; Adagrah, Luke Aniakwo; Adjei-Acquah, Esther; Acquah, Ato Oppong; Ankomah, James; et al.
Summary: Background: Surgical site infection (SSI) is the most common postoperative complication worldwide. WHO guidelines to prevent SSI recommend alcoholic chlorhexidine skin preparation and fascial closure using triclosan-coated sutures, but called for assessment of both interventions in low-resource settings. This study aimed to test both interventions in low-income and middle-income countries. Methods: FALCON was a 2 × 2 factorial, randomised controlled trial stratified by whether surgery was clean-contaminated, or contaminated or dirty, including patients undergoing abdominal surgery with a skin incision of 5 cm or greater. This trial was undertaken in 54 hospitals in seven countries (Benin, Ghana, India, Mexico, Nigeria, Rwanda, and South Africa). Patients were computer randomised 1:1:1:1 to: (1) 2% alcoholic chlorhexidine and non-coated suture, (2) 2% alcoholic chlorhexidine and triclosan-coated suture, (3) 10% aqueous povidone–iodine and non-coated suture, or (4) 10% aqueous povidone–iodine and triclosan-coated suture. Patients and outcome assessors were masked to intervention allocation. The primary outcome was SSI, reported by trained outcome assessors, and presented using adjusted relative risks and 95% CIs. Analysis was by intention to treat. This trial is registered with ClinicalTrials.gov, NCT03700749 . Findings: Between Dec 10, 2018, and Sept 7, 2020, 5788 patients (3091 in clean-contaminated stratum, 2697 in contaminated or dirty stratum) were randomised (1446 to alcoholic chlorhexidine and non-coated suture, 1446 to alcoholic chlorhexidine and triclosan-coated suture, 1447 to aqueous povidone–iodine and non-coated suture, and 1449 to aqueous povidone–iodine and triclosan-coated suture). 14·0% (810/5788) of patients were children and 66·9% (3873/5788) had emergency surgery. The overall SSI rate was 22·0% (1163/5284; clean-contaminated stratum 15·5% [454/2923], contaminated or dirty stratum 30·0% [709/2361]). For both strata, there was no evidence of a difference in the risk of SSI with alcoholic chlorhexidine versus povidone–iodine (clean-contaminated stratum 15·3% [223/1455] vs 15·7% [231/1468], relative risk 0·97 [95% CI 0·82–1·14]; contaminated or dirty stratum 28·3% [338/1194] vs 31·8% [371/1167], relative risk 0·91 [95% CI 0·81–1·02]), or with triclosan-coated sutures versus non-coated sutures (clean-contaminated stratum 14·7% [215/1459] vs 16·3% [239/1464], relative risk 0·90 [95% CI 0·77–1·06]; contaminated or dirty stratum 29·4% [347/1181] vs 30·7% [362/1180], relative risk 0·98 [95% CI 0·87–1·10]). With both strata combined, there were no differences using alcoholic chlorhexidine or triclosan-coated sutures. Interpretation: This trial did not show benefit from 2% alcoholic chlorhexidine skin preparation compared with povidone–iodine, or with triclosan-coated sutures compared with non-coated sutures, in preventing SSI in clean-contaminated or contaminated or dirty surgical wounds. Both interventions are more expensive than alternatives, and these findings do not support recommendations for routine use. Funding: National Institute for Health Research (NIHR) Global Health Research Unit Grant, BD.